2006
DOI: 10.3758/bf03193651
|View full text |Cite
|
Sign up to set email alerts
|

Segment duration as a cue to word boundaries in spoken-word recognition

Abstract: In two eye-tracking experiments, we examined the degree to which listeners use acoustic cues to word boundaries. Dutch participants listened to ambiguous sentences in which stop-initial words (e.g., pot , j jar) were preceded by eens (once); the sentences could thus also refer to cluster-initial words (e.g., een spot , a spotlight). The participants made fewer fixations to target pictures (e.g., a jar) when the target and the preceding [s] were replaced by a recording of the cluster-initial word than when they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
102
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 47 publications
10
102
0
Order By: Relevance
“…In support of the first approach, research has shown that the speech signal contains regularly occurring properties such as the aspiration of word-initial plosives or durational cues, which correlate with word boundaries (Lehiste, 1960;Nakatani & Dukes, 1977) and are exploited by listeners (e.g., Dumay, Content, & Frauenfelder, 1999;Gow & Gordon, 1995;Mattys & Melhorn, 2007;Quené, 1987Quené, , 1992Shatzman & McQueen, 2006;Spinelli, McQueen, & Cutler, 2003). But languages differ in how word boundaries are marked by physical cues, and hence the nature of these cues depends on language-specific phonology (Lehiste, 1964).…”
mentioning
confidence: 99%
“…In support of the first approach, research has shown that the speech signal contains regularly occurring properties such as the aspiration of word-initial plosives or durational cues, which correlate with word boundaries (Lehiste, 1960;Nakatani & Dukes, 1977) and are exploited by listeners (e.g., Dumay, Content, & Frauenfelder, 1999;Gow & Gordon, 1995;Mattys & Melhorn, 2007;Quené, 1987Quené, , 1992Shatzman & McQueen, 2006;Spinelli, McQueen, & Cutler, 2003). But languages differ in how word boundaries are marked by physical cues, and hence the nature of these cues depends on language-specific phonology (Lehiste, 1964).…”
mentioning
confidence: 99%
“…Recently, it has also been demonstrated that rate modulates perception of duration as a suprasegmental lexical-stress cue (Reinisch, Jesse, & McQueen, in press). The present series of experiments investigated speaking rate in relation to another type of durational cue: duration as fine phonetic detail used in word segmentation (e.g., Salverda, Dahan, & McQueen, 2003;Shatzman & McQueen, 2006). We ask whether linearly manipulated speaking rate influences the interpretation of the duration of juncture phonemes, and hence, where word boundaries are perceived in the segmentation of continuous speech.…”
mentioning
confidence: 99%
“…For example in Dutch, "eens speer" ("once spear") and "eens peer" ("once pear") contain the same sequence of sounds but differ in whether the [s] belongs to both words or only the first one. Word boundaries are marked by a variety of acoustic cues that listeners can use (e.g., Cho, McQueen, & Cox, 2007;Mattys, White, & Melhorn, 2005;Nakatani & Dukes, 1977) and duration is an important one of them (e.g., Gow & Gordon, 1995;Klatt, 1976;Quené, 1992;Repp, Liberman, Eccardt, & Pesetsky, 1978;Salverda et al, 2003;Shatzman & McQueen, 2006;Spinelli, McQueen, & Cutler, 2003;Tabossi, Burani, & Scott, 1995). The longer a boundary sound is (e.g., the [s] in the example above), the more it supports a word-initial interpretation (i.e., "eens speer").…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the activation flow of candidate words over time in Fine-Tracker has been successfully linked to word activation in eye-tracking studies 33 that examined the use of durational cues in word recognition. 67,68 A shortcoming of real-speech models is that due to limitations of the speech conversion module, i.e., the imperfect conversion of the speech signal to prelexical representations, such models are currently only able to use a small subset of a language's vocabulary. 63,69 Obviously, if the speech conversion module fails, everything downstream will as well.…”
Section: Fine-trackermentioning
confidence: 99%